VOLATILE COMPOUND ANALYSIS OF AROMATIC RICE MUTANT LINES USING HS-SPME/GC-MS - Muh Riadi; Andi Muliarni Okasa; Rinaldi Sjahril; Meta Mahendradatta; Rafiuddin Rafiuddin (Balai Bioteknologi, Badan Pengkajian dan Penerapan Teknologi (BPPT), 2022)
ABSTRACT Volatile compound is one of the key factors for aromatic components of rice. This study aimed to identify the key aroma components and their relationship with plant productivity in the Pare Bau variety mutant lines and its wild type. Volatile extraction was carried out using the headspace solid-phase microextraction (HS-SPME) method and analysed by the Gas Chromatography-Mass Spectroscopy (GC-MS) instrument. The results of the identification of volatile compounds showed a total of 224 compounds in the mutant lines and wild type. However, only 14 compounds were suspected as key aroma compounds in Pare Bau rice, namely 2-Acetyl-1-pyrroline, Indole, 1-Octanol, 1-Octen-3-ol, 2,4-Nonadienal, (E,E)-, Octanal, 2-Nonenal, (E)-, 2-Octenal, (E)-, Decanal, Hexanal, Nonanal, Furan, 2-pentyl-, toluene and vanillin. The results on aroma compounds of mutant lines using principal component analysis showed that there were differences in the main characteristics of several strains and wild type. There was no relationship between increasing volatile concentration and plant productivity, vice versa. ABSTRAK Senyawa volatil merupakan salah satu faktor kunci sebagai komponen aromatik beras. Penelitian ini bertujuan untuk mengidentifikasi faktor kunci sebagai komponen aroma dan hubungannya dengan produktivitas pada galur mutan dan Pare Bau (genotipe tetua). Ekstraksi senyawa volatil dilakukan dengan metode headspace solid-phase microextraction (HS-SPME) dan dianalisis dengan instrumen Gas Chromatography-Mass Spectroscopy (GC-MS). Hasil identifikasi senyawa volatil menunjukkan sejumlah 224 senyawa yang terdapat dalam galur mutan dan genotipe tetuanya. Namun, hanya 14 senyawa yang diduga sebagai senyawa aroma utama pada beras Pare Bau, yaitu 2-Acetyl-1-pyrroline, Indole, 1-Octanol, 1-Octen-3-ol, 2,4-Nonadienal, (E,E)-, Oktanal, 2-Nonanal, (E)-, 2-Oktenal, (E)-, Dekanal, Heksanal, Nonanal, Furan, 2-pentil-, toluen dan vanilin. Hasil analisis senyawa aroma galur mutan dengan analisis komponen utama menunjukkan adanya perbedaan karakteristik utama dari beberapa galur dengan genotipe tetuanya. Tidak terdapat hubungan antara peningkatan konsentrasi senyawa volatil dengan produktivitas tanaman.